Semiótica y composición en la iconografía religiosa de los siglos - XVI - XVIII en Tunja (2021)
This article presents the main meanings of the iconography that was developed in the province of Tunja, visible in the religious painting of the XVI, XVII and XVIII, centuries. To this end, an analysis of this drawn city and the collective imagery that framed the visual culture of the “Colonial Tunja” is presented. To achieve this, this reflection is divided into three parts. Firstly, the methodological model that was advanced under a propositive approach and an inductive perspective is presented, which emerged from the elimitation of the main religious images present in the city, 96 in total, from these periods. Secondly,a characterization was made that allowed defining the main themes of religious painting, a situation onwhich, a characterization of the main meanings and their contexts was consolidated, to conclude with a reflection on the incidence of these meanings in the social structure. Of the city of Tunja in the period under study that corresponded to the Colonial order of the city.